Marketing de instituciones deportivas: de las relaciones públicas a la valoración de la imagen corporativa como activo intangible - Gastañaduy, Alfonso (2003)
This work seeks to contribute to the development of a better conceptualization of corporate image management applied to sports companies. The theoretical framework presents the evolution of the concepts associated with the image of the company since the emergence of public relations. Then the specific case of the management of large sports activities, which incorporates the modern developments of business management, strongly focused on the management of image and with a clear vocation to apply the theory of reputation; this, in order to ensure that the financial management of intangible assets materializes in a growing and consistent assessment of the "brand" of the sports company or the great international sports competition. Real experiences of successful companies in the field of sports are described.